Channel Estimation in BPSK-QPSK-PSK 16 & 64 QAM MIMO-OFDM System (International Journal of Current Engineering and Technology, 2014)
This paper presents the review of channel estimation in MIMO-OFDM system. The objective of this paper is to show the information about the improvement of channel estimation accuracy in MIMO-OFDM system. The MIMO-OFDM system is the combination of the MIMO technique and OFDM technique, which is enhancing the capacity, improve the link reliability high data rate transmission for future broadband wireless communication and also use for avoid Inter Symbol Interference (ISI).
Keywords: Channel estimation, MIMO OFDM